Burned out and ready to leave? How workplace violence drives turnover among Chinese nurses and the role of well-being HRM - Timothy Bartram; Patricia Pariona-Cabrera; Qinyan Gong; Xiaoyan Liang; Di Fan; Jessica Borg; Hannah Meacham; Tse Leng Tam; Shea Fan; Jillian Cavanagh; Justine Ferrer; Peter Holland (Health Care Management Review, 2026)
Background: Workplace violence is a growing phenomenon in health care settings, which negatively impacts nurses’ physical and mental well-being and intention to leave. Understanding the forces that shape nurses’ intention to leave is therefore fundamental to safeguarding the quality of patient care, patient safety, and system sustainability, a critical and central concern for health care management. Purpose: Against a backdrop of workplace violence, high workloads, and chronic nurse burnout, we test the mediating role of burnout on the relationship between workplace violence and intention to leave. We also test the buffering role of well-being human resource management (WBHRM) on the relationship between burnout and intention to leave, so that higher levels of WBHRM will mitigate the positive relationship between burnout and intention to leave. Methodology/Approach: We test these hypotheses using the conservation of resources (COR) theory and a three-wave matched sample of 179 nurses working in a large Chinese health service. Findings: We confirm one of our two hypotheses. We report that nurse burnout positively mediates the relationship between workplace violence and intention to leave. However, interestingly, we find that WBHRM does not buffer the relationship between nurse burnout and intention to leave but actually exacerbates this relationship. Practical Implications: We discuss the health care management implications of our findings and suggest various possible explanations for WBHRM exacerbating the relationship between burnout and intention to leave. We suggest that health care managers need to understand WBHRM within its wider social context, the proactive use of HRM practices to prevent violence and burnout before significant personal resource loss, and the need for structural changes in hospital settings to tackle systemic workforce challenges such as high workloads and work intensification.